Do Institutions Matter for FDI Spillovers? The Implications of China’s “Special Characteristics” - Du, Luosha (2012)
The authors investigate how institutions affect productivity spillovers from foreign direct investment (FDI) to China's domestic industrial enterprises during 1998-2007. They examine three institutional features that comprise aspects of China's "special characteristics": (1) the different sources of FDI, where FDI is nearly evenly divided between mostly Organization for Economic Co-operation and Development (OECD) countries and Hong Kong (SAR of China), Taiwan (China), and Macau (SAR of China); (2) China's heterogeneous ownership structure, involving state- (SOEs) and non-state owned (non-SOEs) enterprises, firms with foreign equity participation, and non-SOE, domestic firms; and (3) industrial promotion via tariffs or through tax holidays to foreign direct investment. The authors also explore how productivity spillovers from FDI changed with China's entry into the WTO in late 2001. They find robust positive and significant spillovers to domestic firms via backward linkages (the contacts between foreign buyers and local suppliers). The results suggest varied success with industrial promotion policies. Final goods tariffs as well as input tariffs are negatively associated with firm-level productivity. However, they find that productivity spillovers were higher from foreign firms that paid less than the statutory corporate tax rate.